An adult cystic fibrosis patient presenting with persistent dyspnea: case report - Farinet Catherine L; Onady Gary M (BMC Pulmonary Medicine, 2006)
Abstract Background Persistent dyspnea is a common finding in the cystic fibrosis patient that typically leads to further work up of an alternative pulmonary etiology. Adult cystic fibrosis patients; however, are growing in numbers and they are living into the ages in which coronary artery disease becomes prevalent. Coronary disease should be included in the consideration of diagnostic possibilities. Case presentation A 52-year-old white male with cystic fibrosis was evaluated for exertional dyspnea associated with vague chest discomfort. Diagnostic testing revealed normal white blood cell, hemoglobin and platelet count, basic metabolic panel, fasting lipid profile, HbA1c, with chest radiograph confirming chronic cystic findings unchanged from prior radiographs and an electrocardiogram that revealed sinus rhythm with left anterior fascicular block. Stress thallium testing demonstrated a reversible anteroseptal perfusion defect with a 55% left ventricular ejection fraction. Heart catheterization found a 99% occlusion of the left anterior descending artery extending into the two diagonal branches, with 100% obstruction of the left anterior descending artery at the trifurcation and 70% lesion affecting the first posterior lateral branch of the circumflex artery. Conclusion This case report represents the first description in the medical literature of a cystic fibrosis patient diagnosed with symptomatic coronary artery disease. Applying a standard clinical practice guide proved useful toward evaluating a differential diagnosis for a cystic fibrosis patient presenting with dyspnea and chest discomfort.